GENERASI SIAGA: EDUKASI InaRISK DALAM MITIGASI BENCANA MENGHADAPI MEGATHRUST PADA ANAK SDN 2 KAMPUNG BARU - Kurniawan, M. Ari Sofian; Heriany, Melandha; Hayuningrum, Hastari; Putri Ananda, Nabilla (Jurnal Mitrawarga, 2024)
In the face of increasing disaster challenges, especially in disaster-prone areas, it is important to equip the younger generation with appropriate mitigation knowledge and skills. The "Generation of Alerting: InaRISK Education in Disaster Mitigation" program aims to provide understanding of disaster risk and mitigation measures to students of SDN 2 Kampung Baru. Focusing on strengthening children’s capacity to respond to emergency situations, the program is designed to increase their awareness and preparedness of possible megatrust threats. Through interactive and participatory educational methods, it is hoped that students can internalize the concept of disaster mitigation and play an active role in creating a safer environment for themselves and the surrounding community. Data retrieval is done by observation and documentation. The program also aims to establish a network between schools, parents, and communities in a collective effort to reduce disaster risk. By educating the younger generation, it is hoped that a sustainable and responsive disaster alert culture will be created in the future. The results of these activities show that the improvement of students’ understanding is in a high and effective category. This educational service activity has a significant positive impact on the welfare of the younger generation and needs to be maintained and expanded to provide further benefits for the younger generation.